Perencanaan Mesin Perajang Umbi Porang Dengan Pisau Horizontal - Umam, Khoidul; ., Wilarso (Rekayasa Material, Manufaktur dan Energi, 2022)
The compact heat exchanger is one type of heat exchanger which has an area of heat transfer per unit volume the largest (? 400 m2 / m3 for liquids and ? 700 m2 / m3 for gases) which is composed of fin and tube. But often found a decrease in heat transfer performance on a heat exchanger. To increase the heat transfer performance, changes are made on the surface of. Along with the development of science and technology in the field of processing porang tubers. Technology to get production results that are efficient, effective, and innovative in terms of guaranteed work safety increases productivity. The purpose of this study is to facilitate the performance of farmers or agricultural business actors, in the development of porang tuber processing. The method in this research is to design porang tuber cutting tools to become porang chips, which are currently a promising export commodity. To make porang chips, a tool is needed to chop porang tubers with a predetermined thickness. Currently, there are many tubers chopping machines to help make the production process more efficient. However, in the use of these tools, there are still some obstacles, namely the chopper machine is not suitable for all types of tubers, especially porang tubers. This porang tuber has a round shape with varying diameters. And to make Porang Chips, it is necessary to chop with a thickness of 5-7 mm. So to overcome this, a special machine is needed to chop porang tubers with a standard thickness of 5-7 mm. To get effective, efficient results in guaranteed work safety, a porang tuber chopper machine was designed using a horizontal knife. The basic working principle of this machine is to convert the mechanical energy of the driving machine into rotary energy which is used to rotate the blade disc that works horizontally with the aim that the blade can slice continuously and with the same thickness.